Enterprise Productivity Measurement and International Labour Productivity Handbook - Ramsay, M.R. (Sydney, Australia : Advanced Productivity and Quality Centre of Australia (APQCA), 1995)
This book is a very important contribution to the world literature and statistics on productivity, which could be of great importance to many clients - both academicians and practitioners, government officials dealing with productivity policies and statistics and enterprise managers as well as productivity improvement trainers and consultants.
Section A. Enterprise Productivity measurement -- Section B. International labour productivity of economic sectors at country level.
Includes bibliographical references.
Keywords: INDUSTRIAL PRODUCTIVITY -- STATISTICAL METHODS